If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 22 + 3x = -19 + -3x + -22 Reorder the terms: 22 + x + 3x = -19 + -3x + -22 Combine like terms: x + 3x = 4x 22 + 4x = -19 + -3x + -22 Reorder the terms: 22 + 4x = -19 + -22 + -3x Combine like terms: -19 + -22 = -41 22 + 4x = -41 + -3x Solving 22 + 4x = -41 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 22 + 4x + 3x = -41 + -3x + 3x Combine like terms: 4x + 3x = 7x 22 + 7x = -41 + -3x + 3x Combine like terms: -3x + 3x = 0 22 + 7x = -41 + 0 22 + 7x = -41 Add '-22' to each side of the equation. 22 + -22 + 7x = -41 + -22 Combine like terms: 22 + -22 = 0 0 + 7x = -41 + -22 7x = -41 + -22 Combine like terms: -41 + -22 = -63 7x = -63 Divide each side by '7'. x = -9 Simplifying x = -9
| -2x+9-3x=-5(x-2)+2 | | -2x+12-3x=-5(x-2)+0 | | -2x+12-3x=5(x-2)+2 | | 4+3x=7x-24 | | 3(s+2)-(2s-3)=5 | | 3x^2-3x=21 | | 3x+8y+2=0 | | 4x=(-8) | | 5/8*8/5 | | -2x+12-3x=-5(x-2)+3 | | 2x+12-2x=-5(x-2)+2 | | 4x+3y-5=0 | | 8+3x=6x+26 | | -4x+12-2x=-5(x-2)+2 | | x+6-x-4=10-x | | 6x+y=8x-2y | | 4x+2(x+1)=26 | | 12(7X-1)-8(6X+1)+(5X+3)11=23(4X-X)+23 | | -1x+12-3x=-5(x-2)+1 | | 2+3x=5x+24 | | 5/2=17/3 | | 3x+7x=850 | | 0=ln(x^2+5)+0.5x+1 | | -2x+12-2x=-5(x-1)+2 | | -2x+12-2x=-5(x-2)+2 | | 3x+5x=850 | | 12+10=14y-3y | | -2x+10-3x=-5(x-2)+2 | | 8-6x-3=-21+4x-14 | | 7(x+2)=9x+2 | | 2(1x+8)=12 | | 6x^2-12=5x^2-4x |